Method of invigorating spleen and replenishing kidney and resolving phlegm for obesity-type polycystic ovary syndrome: a network meta-analysis and summary of herbal prescription regularity - Lyu, Yueqiao; Cai, Lian; Li, Mingzhu (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to evaluate the therapeutic efficacy of Invigorating Spleen and Replenishing Kidney and Resolving Phlegm Prescription (ISRKRPP) in treating obesity-type polycystic ovary syndrome (PCOS) and to analyze the prescription regularity through data mining technology.MethodsDatabases were retrieved up to September 30, 2024. RCTs on obesity-type PCOS treated with ISRKRPP and Western medicine (WM) were included. The Risk of Bias 2 tool was used for quality assessment. Network meta-analysis was performed using Stata 14.0. After standardizing herb names, a corresponding herbal database was built in Excel. Based on Excel and R language, the core drugs and prescription rules used in the treatment of obese PCOS were analyzed and visualized.ResultsA total of 14 articles, involving 1,163 patients and 7 prescriptions, were included. Network meta-analysis indicated the following: Qihuang Zengmin Decoction + WM may be optimal for overall efficacy (Confidence in Network Meta-Analysis [CINeMA]: moderate confidence); Cangfu Daotan Decoction + WM showed superiority in reducing BMI (CINeMA: moderate confidence); Method of Regulating and Supplementing Spleen and Kidney + WM most effectively improved HOMA-IR (CINeMA: moderate confidence); Cangfu Daotan Decoction + WM best regulated LH (CINeMA: moderate confidence); Heshi Powder + WM medicine most effectively reduced testosterone (CINeMA: moderate confidence). Herbal Regularity analysis revealed core herbs for the treatment included Rhizoma atractylodis, Poria cocos, Angelica sinensis, Pinellia ternata, and Epimedium. The herbal cluster, including Epimedium, Poria cocos, Angelica sinensis, Citrus, Spina gleditsiae, Salviae miltiorrhizae, Rhizoma atractylodis, Pinellia ternata, and Rhizoma cyperi may be the core prescription for the treatment of obesity-type PCOS.ConclusionBased on the results of the present studies, ISRKRPP combined with WM can improve the effect of obesity-type PCOS. Due to the limitations of the present studies, more clinical studies are needed for further validation.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024594257.